Online Citizen Science and the Widening of Academia Distributed Engagement with Research and Knowledge Production - Curtis, Vickie (Palgrave Studies in Alternative Education, 2018)
This book examines the increasing popularity of online citizen science projects arising from developments in ICT and rapid improvements in data storage and generation. As these new technologies allow for much higher levels of participation, collaboration and interaction, the author explores what online citizen science projects reveal about the 'democratisation' of science and distributed engagement with authentic research. Analysing the wider appeal of these projects as well as their potential for informal science learning and creating communities of practice, this book asks whether 'citizen' and 'researcher' will ever be on equal footing. Drawn from years of mixed-methods research, this volume sheds light on this under-researched subject area despite its recent growth and enormous potential. It is sure to be of interest to students and scholars of democratised knowledge, citizen science and online learning, as well as those already involved in citizen science.